1983
DOI: 10.1002/chin.198321014
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: AC‐IMPEDANCE MEASUREMENTS ON ALUMINUM BARRIER‐TYPE OXIDE FILMS

Abstract: AC‐Impedanzmessungen an relativ dünnen Sperrschichtfilmen im Frequenzbereich 5·10‐3 Hz ⩽ f ⩽ 104 Hz im System polykristallines reines Al/0.16 M NH4‐tartrat bei pH 5‐7 im Potentialbereich ‐900 mV ⩽ EH ⩽ 400 mV zeigen, daß derartige Messungen eine wirksame Möglichkeit darstellen, um Informationen zu den Eigenschaften und der Kinetik passivierter Phasengrenzen zu erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…(b) Nyquist plottwo parts: a capacitive loop occurring in relatively high-frequency region and an inductive loop present in a low-frequency region. The spectra from this study are in good agreement with those obtained in previous studies (Ref[35][36][37][38][39].Cao (Ref 40) suggested that these types of spectra could be described by the equivalent circuit inFig. 6under the following conditions: A <0, B> 0, and D-RtlAI > 0.…”
supporting
confidence: 90%
“…(b) Nyquist plottwo parts: a capacitive loop occurring in relatively high-frequency region and an inductive loop present in a low-frequency region. The spectra from this study are in good agreement with those obtained in previous studies (Ref[35][36][37][38][39].Cao (Ref 40) suggested that these types of spectra could be described by the equivalent circuit inFig. 6under the following conditions: A <0, B> 0, and D-RtlAI > 0.…”
supporting
confidence: 90%
“…According to Rammelt 23 the dispersive behavior observed at rough electrodes can be described by a constant phase element (CPE). The impedance of this element is given by Equation 1: [23,24] (1)…”
Section: Resultsmentioning
confidence: 99%
“…The time constant at high frequencies The reason for the different time constants as yet is unclear. Bessone et al (1983) indicated that the high frequency time constant could be attributed to the oxide layer on the steel. Brett (1990) reported that this time constant could be assigned to the interfacial reactions.…”
Section: Electrochemical Impedance Resultsmentioning
confidence: 99%